Offshore Technology Conference 1978
DOI: 10.4043/3163-ms
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Fatigue Analysis of Murchison Tower Structure

Abstract: The Murchison structure is~barge-launched steel drilling and production platform which is to be floated out in Spring 1979 and installed in the Northern North Sea in 156m of water-~-Refel'em~es 2nd. illustrations a.t end. of ];Ja];Jer.In addition, a transient analysis using a Newmark-S integration scheme has been undertaken to establish the dynamic amplification factors by comparison with the base reactions and deck level deflections for corresponding static load cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Former research use straight pipe as a model. As used by Hallam [4] stated that piping system failure often occured in bending area which produce maximum stress. And field experience shown that pipe has many types of bend, tee and angle variations.…”
Section: Introductionmentioning
confidence: 99%
“…Former research use straight pipe as a model. As used by Hallam [4] stated that piping system failure often occured in bending area which produce maximum stress. And field experience shown that pipe has many types of bend, tee and angle variations.…”
Section: Introductionmentioning
confidence: 99%